TATA KELOLA, AKUNTABILITAS DAN OPTIMALISASI ADMINISTRASI PAJAK DAERAH: KAJIAN PUSTAKA TERHADAP PRAKTIK PEMERINTAH DI NEGARA BERKEMBANG - Loso Judijanto (ADMIN: Jurnal Administrasi Negara, 2026)
This article analyses the relationship between good governance, fiscal accountability, and optimisation of local tax administration in developing countries through a systematic literature review approach. The results of the study found that weak transparency and administrative corruption significantly hamper the contribution of local taxes to local revenue (PAD), with potential leakage of up to 30% of fiscal potential. Technological reforms such as e-filing, digital payments, and data analytics—such as Pajak Menyapa Kendari and Palembang e-tax—have been proven to increase operational efficiency by 15–30% and taxpayer compliance through real-time information transparency. Key findings confirm the synergy of two dimensions: accountable governance creates institutional legitimacy, while technological innovation provides the operational infrastructure to reduce fiscal dependence on central transfers. Structural challenges include the digital divide, low literacy, and weak central-regional coordination, which require a holistic approach based on human resource capacity and supporting regulations. Policy implications include strengthening public audits, digital training for tax officials, and stakeholder engagement to create a virtuous cycle: increased PAD → improved services → public trust. This study contributes to the subnational fiscal governance literature with an integrative model for sustainable local tax reform in developing countries.